Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Deep Learning pada Materi Lingkaran Kelas XI - Devita Nanda Oktavia; Abd. Basir Abbas; Safrudiannur Safrudiannur; Tri Widyasari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This development research was motivated by problems in mathematics learning at SMA Negeri 5 Samarinda, which is still dominated by formula memorization (surface learning), resulting in students’ limited conceptual understanding, particularly on circle material. This study aimed to determine the development process of deep learning-based student worksheets (LKPD) on circle material and to identify the validity and practicality level of the developed LKPD. This research employed the Research and Development (R&D) method using the 4D model, which consists of the Define, Design, Develop, and Disseminate stages. The instruments used included validation sheets from material experts and media experts, as well as practicality questionnaires completed by teachers and students. The data were analyzed using the Aiken’s V index. The results showed that the LKPD was developed through needs and curriculum analysis, design integrating the deep learning framework, validation, revision, and field testing. The LKPD was declared valid by experts with an average Aiken’s V index of 0.798 (valid category) and highly practical by teachers and students with an average Aiken’s V index of 0.968 (very valid category). Therefore, the developed deep learning-based LKPD is feasible and highly practical for use in mathematics learning on circle material for Grade XI.